Oil, power, and war : a dark history - Auzanneau, Matthieu (Chelsea Green Publishing, 2018)
"Oil, Power, and War is a sweeping, unabashed history of oil, told by French journalist Matthieu Auzanneau. It provides a detailed account of the people and events that drove the oil industry from its earliest days, and takes a critical look at the way oil interests have commandeered politics and economies, changed cultures, disrupted power balances across the globe, and spawned wars. The author exposes the greed and reckless behavior--by a long line of characters from John D. Rockefeller to Dick Cheney--that moved oil along its destructive, unsustainable path, from its heyday when the first oil wells were drilled to the quest for new sources as old ones dried up. The author traces the rise of the Seven Sisters and other oil cartels, and follows the thread of oil through the crises that have shaped our times: two world wars, the Cold War, the Great Depression and the 2008 financial crash, oil shocks, wars in the Middle East, the race for Africa's oil riches, and more. We learn lesser-known stories, too, like how New York City taxes were once funneled directly to banks run by oil barons, after the city was about to default on its debt. And we gain new perspective on the central role of oil in military conflicts over the past 100 years. Now that there is much less oil available, Auzanneau looks to the future and warns that even greater conflict may arise"--